What Influences Capital Adequacy Ratio in Islamic Commercial Banks? Evidence from Indonesia - Mursal Mursal; Darwanis Darwanis; Ridwan Ibrahim (Journal of Accounting Research, Organization and Economics, 2019)
AbstractObjective – This study aims to examine whether Return on Assets (ROA), Financing to Deposit Ratio (FDR), Size, Net Interest Margin (NIM), and Deposit (DEP) have any influence on Capital Adequacy Ratio (CAR) of Islamic Commercial Banks in Indonesia for the period of 2015-2017. Design/methodology – The population in this study is all Islamic Commercial Banks operating in Indonesia for the period 2015-2017. The data was collected from financial statements of the Islamic Commercial Banks for the period of three years totalling of 36 observations. Multiple Linear Regression was used to analyse the data. Results – The results showed that Return on Assets (ROA) has a negative effect on Capital Adequacy Ratio (CAR). Meanwhile financing to Deposit Ratio (FDR) has a negative effect on Capital Adequacy Ratio (CAR) and size has a negative effect on Capital Adequacy Ratio (CAR). Furthermore, net Interest Margin (NIM) has a positive effect on Capital Adequacy Ratio (CAR) and lastly Deposit (DEP) has a negative effect on Capital Adequacy Ratio (CAR). Research limitations/implications – This study has limitations due to the short observation period of only 3 years from 2015 to 2017. Future studies are recommended to enhance this current study by embarking a longer period of study or by performing a comparative analysis between Islamic banks in different countries.